PENGARUH PROFITABILITY, FIRM SIZE, TANGIBILITY DAN GROWTH OPPORTUNITY TERHADAP CAPITAL STRUCTURE - Yensen Kusno, Jonnardi (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study was to determine the effect of Profitability, Firm Size, Tangibility, and Growth Opportunities on Capital Structure in Manufacturing Companies on the Stock Exchange in the 2014-2018 period. This study uses 38 companies that have been selected using the purposive sampling method for 5 years, namely 2014,2015,2016,2017 and2018. The data processing uses Eviews version 10. The results show Profitability, Firm Size, Tangibility, Growth Opportunities have an influence on the Structure Capital.